Discovering educational augmented reality math applications by prototyping with elementary-school teachers - Radu, Iulian; McCarthy, Betsy; Kao, Yvonne (Proceedings of the Workshop on Future Trends of Distributed Computing Systems, 2016)
In recent years, augmented reality (AR) applications for children's entertainment have been gaining popularity, and educational organizations are increasingly interested in applying this technology to children's educational games. In this paper we describe our collaboration with teachers and game designers, in order to explore educational potential for AR technology. This paper specifically investigates the topics of: What mathematics curriculum topics should technological innovations address in the Grade 1-3 classrooms? Which of the topics are suitable for AR games? And, how can we facilitate an efficient dialogue between educators and game designers?